1999
DOI: 10.1021/ja9824831
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Predictions and Single-Crystal Neutron Diffraction and Inelastic Neutron Scattering Studies on the Reaction of Dihydrogen with the Dinuclear Dinitrogen Complex of Zirconium [P2N2]Zr(μ-η2-N2)Zr[P2N2], P2N2 = PhP(CH2SiMe2NSiMe2CH2)2PPh

Abstract: A single-crystal neutron diffraction analysis along with density functional calculations and incoherent inelastic neutron scattering studies has conclusively shown that the dihydrogen adduct of [P 2 N 2 ]Zr(µ-η 2 -N 2 )-Zr[P 2 N 2 ] (1) (where P 2 N 2 ) PhP(CH 2 SiMe 2 NSiMe 2 CH 2 ) 2 PPh) is [P 2 N 2 ]Zr(µ-η 2 -N 2 H)(µ-H)Zr[P 2 N 2 ] (2), the complex with a bridging hydride and a N-N-H moiety, and not the dihydrogen complex [P 2 N 2 ]Zr(µ-η 2 -N 2 )(µ-η 2 -H 2 )Zr[P 2 N 2 ] (3), as was proposed on the basis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(46 citation statements)
references
References 26 publications
4
41
0
1
Order By: Relevance
“…Indeed, the HOMO, the p-bonding orbital of the MaN 2 aM fragment, is expected to donate electrons to the s u * orbital of the incoming H 2 molecule, while the LUMO, s (s and d)-orbitals of metal centers, is required to interact with the s g -bonding MO of the reacting H 2 molecule. This qualitative orbital picture is consistent with the ''metathesis'' transition state (involving one of the M and N atoms of the complex, and two H-atoms of H 2 , see Figure 4.2) reported for H 2 addition to di-Zr-N 2 complexes [38,39,48]. …”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…Indeed, the HOMO, the p-bonding orbital of the MaN 2 aM fragment, is expected to donate electrons to the s u * orbital of the incoming H 2 molecule, while the LUMO, s (s and d)-orbitals of metal centers, is required to interact with the s g -bonding MO of the reacting H 2 molecule. This qualitative orbital picture is consistent with the ''metathesis'' transition state (involving one of the M and N atoms of the complex, and two H-atoms of H 2 , see Figure 4.2) reported for H 2 addition to di-Zr-N 2 complexes [38,39,48]. …”
Section: Introductionsupporting
confidence: 85%
“…Subsequent detailed computational studies [38][39][40]48] have revealed that this reaction occurs via a ''metathesis'' transition state (Figure 4.2). More importantly, the computational studies have suggested the possibility of the addition of several (more than one) H 2 molecules to a di-Zr complex under appropriate conditions [38][39][40].…”
Section: Introduction 85mentioning
confidence: 99%
“…[90,91] These protonation reactions have been discussed previously. [1,3] Several new examples of protonation of metal N 2 complexes have arisen.…”
Section: Formation Of N à H Bonds From Coordinated Dinitrogenmentioning
confidence: 91%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] In particular,Z r II and Hf II species have been found to display spectacular reactivity in the cleavage of dinitrogen,a nd in the further functionali-zationo ft he activated species. Landmark discoveries in this field have been reported by Fryzuk, [20][21][22][23][24][25][26][27][28] Chirik, [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] and coworkers.…”
Section: Introductionmentioning
confidence: 89%